A self-recombining bacterial artificial chromosome and its application for analysis of herpesvirus pathogenesis - Smith, Gregory A. (The National Academy of Sciences, 2000)
A self-recombining bacterial artificial chromosome (BAC) containing the 142-kb pseudorabies virus genome was constructed such that the viral genome is rapidly excised from the BAC vector backbone on delivery into mammalian cells. The recombination is mediated by loxP sites in the plasmid and Cre recombinase encoded within the BAC vector. A synthetic intron inserted in the middle of the cre ORF completely inhibits recombination in Escherichia coli, but is spliced out after delivery of the plasmid into mammalian cells. Recombination is efficient, and pure virus lacking the BAC vector backbone is immediately isolated from transfected mammalian cells without the need of serial passage or plaque purification.